Isolation and characterization of the sucrose 6-phosphate hydrolase gene from Streptococcus mutans. - Hayakawa, M (1986)
The Streptococcus mutans GS-5 gene, scrB, coding for sucrose 6-phosphate hydrolase activity has been cloned into Escherichia coli utilizing the bacteriophage replacement vector lambda L47.1. DNA sequences containing the gene were initially subcloned into the moderate-copy-number plasmid vector pLG339 to yield active subclones. However, due to the instability of the resultant chimeric plasmids, the gene was subsequently subcloned into the low-copy-number vector pOU61 to yield the stable hybrid plasmid pMH613. Both plasmids contain a 6.6-kilobase EcoRI fragment from strain GS-5 and express both hydrolase and sucrase activities. The relative position of the gene in the insert has been determined after Tn5 mutagenesis and deletion analysis. The cloned enzyme was purified to near homogeneity after gel filtration and anion-exchange chromatography, chromatofocusing, and preparative polyacrylamide gel electrophoresis. The purified enzyme displayed a molecular mass of 58 kilodaltons, which is significantly higher than the 48-kilodalton enzyme previously purified from S. mutans GS-5. These results suggest that processing of the hydrolase occurs in S. mutans.